Исследование влияния нагрева на упругое пружинение при пластическом изгибе двухслойных листов - Загорянский, В. Г. (НТУ "ХПИ", 2014)
Статья посвящена теоретическому анализу и экспериментальному исследованию влияния нагрева при гибке двухслойных листов на их упругое пружинение. Получены расчетные зависимости для определения пружинения при нагреве двухслойных листов (полос) при гибке. Для двухслойных листов коррозионностойкого биметалла 09Г2С + 12Х18Н10Т установлены зависимости угла пружинения от температуры нагрева двухслойных листов под гибку плакирующим слоем наружу и внутрь и определены оптимальные температуры нагрева.

The paper to theoretical analysis and experimental research of influence of heating at bending of two-layered sheets on their elastic springback is devoted. In the paper dependences for calculation of elastic springback at heating of double-layer sheets (stripes) at bending developed. It is established that temperature of heating effects on change of curvature of sheet because of elastic bending through change of the value of the modulus of elasticity and constants of curve of strengthening. For the double-layer sheets of corrosive-proof bimetal of 09Г2С + 12Х18Н10Т dependences of angle of springback on the temperature of heating of double-layer sheets under bending by a cladding outside and inward are established and the optimal temperatures of heating are determined.
Investigation of the effect of heat on the spring-elastic plastic bending with two-layer sheets
Keywords: пластический изгиб; двухслойный лист; упругое пружинение; влияние нагрева; plastic bending; two-layer sheet; bending moment; elastic springback; influence of heating